Meningkatkan Sikap Percaya Diri Dengan Storytelling Dan Perilaku Hidup Bersih Dan Sehat Anak – Anak di Lingkungan XVII Pasar 2 Barat, Kelurahan Rengas Pulau, Kecamatan Medan Marelan, Medan – Sumatera Utara - Kresna Ningsih Manik; Merry Susanty Br Tarigan; Dolli Rotua Sinaga; Yenita Br Sembiring; Nurmahyuni Asrul; Jamaluddin Nasution; Fachri Yunanda; Jonris Tampubolon (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Storytelling is a powerful way to communicate, inspire, and connect people and is an invaluable tool for preserving cultural heritage, building cross-cultural understanding, and celebrating the diversity of human experience. In implementing the activity, several steps are applied to carry out storytelling, namely: Selecting and compiling stories that children like, Understanding the story you want to tell, Making body movements, Using a clear voice/intonation, Using appropriate facial expressions, Paying attention to eye contact with the audience. The learning of storytelling to children is expected to be able to build the children’ self-confidence and language ability and other purposes. Using props, apart from teaching storytelling to children in the XVII Pasar 2 Barat neighborhood, the lecturer team also teaches the importance of a healthy lifestyle. Teaching children a healthy lifestyle is a long-term investment in their health and well-being. Some of the tips given by the initiators of the activities to children in Ward -children to limit Screen Time, Teach children to have Good Sleep Habits, Teach children to choose activities they like, Teach Personal Hygiene Habits. Through a positive, consistent and involving approach, children can help them understand and implement healthy lifestyles from an early age. This helps create positive habits that they can carry into adulthood. By providing a good understanding of healthy lifestyles, children can grow into individuals who are aware of the importance of maintaining their own health and well-being.